Leptin and Nutritional Markers in Childhood Protein-Energy Malnutrition - ERBAGCI*, A.B.; KILINÇ†, M.; TARAKÇIOGLU, M.; TAYSI, S.; KOCABAS, R. (Asian Journal of Chemistry, 2009)
Leptin is an important signal in metabolic/endocrine adaptation to prolonged nutritional deprivation. This cross-sectional study was performed to determine alterations associated with protein-energy malnutrition in serum levels of leptin and classical nutritional markers. Forty-two children with protein-energy malnutrition was classified according to Gomez and 21 healthy controls were recruited. Serum leptin, albumin, prealbumin, fibronectin, transferrin, lipoprotein (a) and whole blood hemoglobin concentrations were determined. Leptin levels were significantly lower in undernourished children, declining with degree of malnutrition. Alteration of albumin, hemoglobin and lipoprotein (a) became apparent at late stages of malnutrition. Gomez classification was the only significant contributor to the variations in leptin concentrations among age, weight, presence of infection, breast-feeding duration and age at feeding with complementary foods. This study provides evidence that leptin is sensitive to stages of malnutrition independent of body weight, probably for it's role in metabolic adaptation. Serum prealbumin, transferrin and fibronectin does not offer a sensitive alternative in the background of increased susceptibility to infection.